The PRISMA statement for reporting systematic reviews and meta-analyses of studies that evaluate health care interventions: explanation and elaboration (Italian Journal of Public Health, 2009)
Systematic reviews and meta-analyses are essential to summarize evidence relating to efficacy and safetyof health care interventions accurately and reliably. The clarity and transparency of these reports, however,is not optimal. Poor reporting of systematic reviews diminishes their value to clinicians, policy makers, andother users. Since the development of the QUOROM (QUality Of Reporting Of Meta-analysis) Statement—areporting guideline published in 1999—there have been several conceptual, methodological, and practicaladvances regarding the conduct and reporting of systematic reviews and meta-analyses. Also, reviews ofpublished systematic reviews have found that key information about these studies is often poorly reported.Realizing these issues, an international group that included experienced authors and methodologistsdeveloped PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) as an evolution ofthe original QUOROM guideline for systematic reviews and meta-analyses of evaluations of health careinterventions. The PRISMA Statement consists of a 27-item checklist and a four-phase flow diagram. Thechecklist includes items deemed essential for transparent reporting of a systematic review. In thisExplanation and Elaboration document, we explain the meaning and rationale for each checklist item. Foreach item, we include an example of good reporting and, where possible, references to relevant empiricalstudies and methodological literature. The PRISMA Statement, this document, and the associated Web site(http://www. prisma-statement.org/) should be helpful resources to improve reporting of systematicreviews and meta-analyses.